Extent of Disclosures on Halal Assurance Management System (HAMS): Cases of Halal Certified Companies Listed on Bursa Malaysia - Mohd Khairuddin A. Mulok; Zurina Shafii (Universiti Sains Islam Malaysia, 2024)
e-Proceedings of The 9th Islamic Banking, Accounting and Finance International Conference 2020 (iBAF2020) “Navigating the New Normal in Islamic Finance and Wealth Management” 10th – 11th November 2020, Malaysia Organized by: Faculty of Economics and Muamalat,USIM Page: 211-217